Pelatihan Pengelolaan Limbah Minyak Jelantah menjadi Lilin Hias sebaga Upaya Peningkatan Pengetahuan dan Keterampilan Masyarakat Desa Labuhan Sumbawa - Nurlaila Agustikawati; Fitri Setianingsih; Desy Fadilah Adina Putri (Institut Teknologi dan Bisnis Semarang, 2024)
The high consumption of cooking oil in daily life and food preparation both at the household level and in the food industry has resulted in an increasing amount of used cooking oil waste being produced. When the public is educated about the dangers of used cooking oil, there will be an increase in knowledge and awareness not to use used cooking oil again. However, this actually results in negative behavior in the community in managing used cooking oil waste which actually has a bad impact on the environment. This behavior includes used cooking waste from households that is thrown into the trash or thrown directly into the gutter. This can pollute the environment and if it is thrown into the dishwashing sink it will also clog the pipes. This behavior can be minimized by training in managing used cooking oil waste into decorative candles with economic value. This activity is carried out using counseling, demonstration and training methods. The result of this service activity is an increase in community skills in managing used cooking oil waste. So it is hoped that education and training like this can continue to be carried out